TINJAUAN HUKUM ISLAM TERHADAP PRAKTIK JUAL BELI PERALIHAN PIUTANG CESSIE: STUDI DI PT. UNITEC INDO PRATAMA SURABAYA - Dani El Qori (MIYAH : Jurnal Studi Islam, 2023)
Abstract: The Covid-19 pandemic that hit the world from 2020 to 2022 has had an impact on all lines of human life. As a result, many business man have suffered losses. Losses for business man have an impact on the number of bad loans in banks. Some banks sell their debtors' receivables to cessie companies in order to get fresh funds easily and quickly. In this article, we will examine in more depth the practice of buying and selling receivables transactions carried out by PT. BTN Sidoarjo branch to PT Unitec Indo Pratama and review of Islamic law on the transaction. The author uses the theory of baiuddayn and hawalah contracts to analyze the practice of selling these receivables. based on the author's analysis, the sale of receivables transactions carried out by PT. BTN Sidoarjo branch is an illegal transaction in the perspective of Islamic law, using both hawalah and baiuddayn contracts. Keywords: transition, receivable, subrogation, eve